Implementation Of A Virtual Account System In Improving School Administrative Payment Order: A Case Study At SMP Zainul Hasan 1 Genggong - Kurrotu Aini; Maula Nasrifah; Moh. Abd. Rahman (CV Putra Publisher, 2026)
The development of information and communication technology has driven the transformation of school financial administration through the implementation of a virtual account system to improve the orderliness of school administrative payments, efficiency, and transparency. This study aims to analyze the implementation of a virtual account system in improving the orderliness of school administrative payments at SMP Zainul Hasan 1 Genggong and identify the benefits and obstacles faced. This study used a qualitative approach with a case study type. Data were collected through interviews, observations, and documentation involving the principal, administrative staff, and parents. The results showed that the virtual account system was able to improve the orderliness of school administrative payments, as indicated by an increase in timely payments from 63% to 80%. This system also increased administrative efficiency through automatic recording and real-time verification and supported transparency in financial management. The main obstacles identified were limited digital literacy and internet access. Overall, the virtual account system made a significant contribution to improving the orderliness of school administrative payments, efficiency, and transparency in school financial administration.